Isolation and Characterization of Potential Salmonella Phages Targeting Multidrug-Resistant and Major Serovars of Salmonella Derived From Broiler Production Chain in Thailand - Pelyuntha, Wattana; Ngasaman, Ruttayaporn; Yingkajorn, Mingkwan; Chukiatsiri, Kridda; Benjakul, Soottawat; Vongkamjan, Kitiya (Frontiers in Microbiology, 2021)
Salmonella is a major foodborne pathogen that causes foodborne disease in humans through consumption of contaminated foods, especially those with animal origin. Multiple Salmonella strains are antibiotic-resistance due to the commonly use of antibiotics in farm animals, including broiler farms. In this study, an alternative strategy using phage-based treatment was evaluated against Salmonella isolated from the broiler production. The prevalence of Salmonella spp. showed up to 46.2% and 44.4% in bedding samples from the broiler farms located in eastern and southern Thailand, respectively. Overall, 21 samples (36.20%) were positive for Salmonella and 8 serovars were recovered from cloacal swabs, bedding materials (rice husk), and boot swabs collected from five farms. Up to 20 Salmonella phages were isolated from seven water samples from wastewater treatment ponds, a river, and a natural reservoir in Songkhla province. Isolated phages were investigated their lysis ability on 8 target Salmonella serovars derived from broiler farms, 5 serovars from foodborne outbreak-related, and 10 serovars of multidrug-resistant (MDR). All phages showed a strong lytic ability against 5 serovars of Salmonella derived from broiler farms including Kentucky, Saintpaul, Schwarzengrund, Corvalis, and Typhimurium, 3 serovars of foodborne outbreak including Enteritidis, Typhimurium, and Virchow, and 8 serovars of MDR including Agona, Albany, Give, Kentucky, Typhimurium, Schwarzengrund, Singapore, Weltevreden. Three phages with the highest lysis potential including vB_SenS_WP109, vB_SenS_WP110, and vB_SenP_WP128 were selected for a phage cocktail preparation. Overall, a phage cocktail could reduce Salmonella counts by 2.2 to 2.8 log units at 6 h of treatment. Moreover, Salmonella did not develop a resistant pattern after treated with a phage cocktail. Findings here suggest that a phage cocktail is an effective biocontrol to combat Salmonella derived from broiler production chain, other serovars linked to foodborne outbreaks, and MDR.